Impacts of Body Condition Score at Initiation of the Breeding Season on Reproductive Performance and Overall Productivity of Bos Taurus and B. Indicus Beef Cows - Brandao, Alice (2021)
Texas A&M Univ, College Stn, TX 77843 USA